Bandits, borderlands and opium wars: Afghan state-building viewed from the margins - Jonathan Goodhand (Danish Institute for International Studies (DIIS), 2009)
The drugs economy has been an important part of the story of borderland transformation in Afghanistan. Because of drugs, borderlands are no longer marginal, but have become a resource to be exploited by the centre of the fragile state. This Working Paper explores the linkages between the drugs economy, borderlands and 'post conflict' state-building in Sheghnan, a remote district on the Afghan-Tajik border in the north-east Afghanistan. It does this through a fine grained historical analysis of Sheghnan. As such the paper argues that examining the frontier may throw light on processes of state formation, state collapse and 'post conflict' state-building. A focus on borderlands means taking seriously the 'politics of place' and examining the diffuse dynamics and localised projects that feed into and shape processes of state formation.
Keywords: 330; Staatsgründung; Drogenwirtschaft; Grenzgebiet; Afghanistan